PENGARUH VARIASI KONSENTRASI LIMBAH TERHADAP PENURUNAN KANDUNGAN TEMBAGA PADA PENGOLAHAN LIMBAH CAIR PROSES ETCHING DENGAN METODE ELEKTROLISIS - Fifin Hindarti (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2018)
The waste water of copper board etching process in Printed Circuit Board (PCB) production is kind of heavy metal waste water, that is copper, which has not been treated yet. In order to prevent the environment contamination process the waste water should be treated before thrown to environment. The kind of waste water treatment that will be applied to the waste water with heavy metal content, specially copper metal (Cu) is electrolysis method. The experiment was done in laboratory scale. The batch electrolysis reactor was used in this experiment, with the copper as katoda and stainless steel as anoda. Electrolysis process was conducted with waste concentration variation that was equal to 124,16; 110,96 ; and 35,84 ppm. The result of the experiment shows that, the electrolysis methode could reduce copper concentration in the waste water of etching process. The biggest efficiency degradation for the variation of waste concentration was happened at waste concentration 35,84 ppm, that was equal to 100%, with end result equal to 0 ppm. Waste concentration equal to 124,16 of ppm its result 96,24 ppm, and for concentration 110,96 ppm was got by result 0,35 ppm.